Sosialisasi Pengelolaan Emosi Di Masa Remaja Pada Siswa Kelas 10 Dan 11 Di SMK Al-Hikmah Tarogong Garut - Faatinisa, Esty; Dewi, Pretty Shafira; Kurniawan, Naufal Najmii; Audia, Delva Trya; Faozi, Ahmad; purnama, Asvy Wali; Putra, Alif Azhar; Maulana, Adi; Shifa, Bella Rahma (Yayasan Cendekia Gagayunan Indonesia, 2024)
Emotion management is a crucial aspect of adolescent development, often characterized by significant physical, social, and emotional changes. This study aims to enhance the understanding of emotion management among 10th and 11th-grade students at SMK Al-Hikmah Tarogong Garut. The research employs a qualitative method, utilizing data collection through observations and interviews. The findings indicate that many students are unaware of the complexities of their emotions, tending to associate emotions solely with feelings of anger or sadness. Through socialization efforts that include definitions, types, and techniques for managing emotions, students began to recognize and understand various forms of emotions. After the socialization, there was a significant improvement in students' ability to identify emotions and respond positively. This research underscores the importance of emotion management for adolescents in enhancing mental well-being, fostering healthy social relationships, and reducing the risk of mental health issues such as anxiety and depression during adolescence.